PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MENGGUNAKAN PENDEKATAN OPEN-ENDED DENGAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Nurvita (Mat-Edukasia, 2018)
This study aims to determine and describe the differences in mathematical problem solving abilities using an open-ended approach with contextual teaching and learning (CTL) VIII grade students of SMP N 2 Merangin 2016/2017 Academic Year. This study uses a quantitative approach with the experimental method. The study design was a post test only control design with a population of class VIII students totaling 5 classes. The sampling technique uses simple random sampling. The selected sample is class VIII C and class VIII A. The technique of collecting data uses a test in the form of essay questions. The data analysis technique uses the t-test because the data is normally distributed and has a homogeneous variance. From the results of testing the hypothesis it can be concluded that there is a significant difference between mathematical problem solving abilities using an open-ended approach with contextual teaching and learning (CTL) VIII grade students of SMP N 2 Merangin 2016/2017 academic year. Keywords: mathematical problem solving ability, open-ended, contextual teaching and learning (CTL)